Electroforming of Copper and Nickel and Electroplating of Chromium (Chemical Engineering Research Bulletin, 2008)
Experimental investigations were carried out for determining the optimum operating condition or electroforming of copper and nickel as well as for chromium electroplating. For copper and nickel electroforming, high current density deposition was obtained with the agitation of electrolyte by air, cathode movement and use of additive agent. The cathode efficiency increases with the increase in electrolyte composition at low current density. Electroplating of chromium was carried out at low cathode current efficiency and the current efficiency decreases as the electrolyte concentration increases.Chemical Engineering Research Bulletin 10 (2006) 53-63